2001
DOI: 10.1084/jem.193.4.471
|View full text |Cite
|
Sign up to set email alerts
|

Cis3/Socs3/Ssi3 Plays a Negative Regulatory Role in Stat3 Activation and Intestinal Inflammation

Abstract: Immune and inflammatory systems are controlled by multiple cytokines, including interleukins (ILs) and interferons. These cytokines exert their biological functions through Janus tyrosine kinases and signal transducer and activator of transcription (STAT) transcription factors. We recently identified two intrinsic Janus kinase (JAK) inhibitors, JAK binding protein (JAB; also referred to as suppressor of cytokine signaling [SOCS1]/STAT-induced STAT inhibitor [SSI1]) and cytokine-inducible SH2 protein (CIS)3 (or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
357
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(393 citation statements)
references
References 38 publications
33
357
1
2
Order By: Relevance
“…The combination of soluble IL-6 receptor (sIL-6R) and IL-6 stimulates cells that only express gp130 and not IL-6R, a process known as trans-signaling. IL-6 signaling through STAT3 has been extensively studied (Suzuki et al, 2001;Mudter and Neurath, 2007;Tian et al, 2011). This system plays a central role in several immunologic reactions during the development of IBD, and circulating levels of IL-6 and sIL-6R correlate with many clinical features of CD and UC (Mitsuyama et al, 1995;Van Kemseke et al, 2000;Scheller et al, 2006;Rose-John et al, 2009).…”
Section: Il-6 and Stat3mentioning
confidence: 99%
“…The combination of soluble IL-6 receptor (sIL-6R) and IL-6 stimulates cells that only express gp130 and not IL-6R, a process known as trans-signaling. IL-6 signaling through STAT3 has been extensively studied (Suzuki et al, 2001;Mudter and Neurath, 2007;Tian et al, 2011). This system plays a central role in several immunologic reactions during the development of IBD, and circulating levels of IL-6 and sIL-6R correlate with many clinical features of CD and UC (Mitsuyama et al, 1995;Van Kemseke et al, 2000;Scheller et al, 2006;Rose-John et al, 2009).…”
Section: Il-6 and Stat3mentioning
confidence: 99%
“…It is interesting to note that STAT3 was also found to be highly tyrosine phosphorylated in epithelial and lamina propria cells of human ulcerative colitis and Crohn's disease patients as well as in dextran sulfate sodium (DSS)-induced colitis in mice [55], possibly indicating a potential role of STAT3 in epithelial cells during colitis generation.…”
Section: The Stat Signaling Pathwaymentioning
confidence: 99%
“…Indeed, several recent studies have focused on the role of STATs on IBD. Among STATs, the role of STAT3 in IBD has been most well documented by recent studies obtained from human IBD studies [6][7][8] and experimental IBD models [9][10][11][12] . These studies have revealed that STAT3 is in a unique position for pathogenesis of IBD, because STAT3 plays distinct roles between innate immune cells and acquired immune cells.…”
Section: Introductionmentioning
confidence: 99%